(untitled) (Asian Journal of Social Science Studies, 2022)
China’s overall victory in the fight against poverty is a great miracle in human anti-poverty history. Even so, from the perspective of anti-poverty and poverty governance, even though China’s per capita income level has reached the standard of high-income countries as defined by the World Bank, and efforts have been made to overcome the "threshold effect", urban-rural and regional disparities still exist, and China is still a developing country. Therefore, the difficulty of anti-poverty and poverty management will remain in the future. The problem of poverty will be multidimensional, multi-subject, complex, long-term, and systematic. Therefore, the construction of an open, synergistic and sustainable anti-poverty ecosystem with multiple subjects will help anti-poverty and poverty governance to be able to change from super-regular to regular and help the continuation and continuous optimization of the big poverty alleviation pattern. This paper combines the user experience of China’s anti-poverty attack with the specific requirements of rural revitalization and proposes policy recommendations for consolidating the results of the anti-poverty attack and implementing rural revitalization.